Chinese medical students and residents' perspectives on medical education for professional role formation: an exploratory cross-sectional study. Issue 1 (October 2019) - Fan, Lihong; Kosik, Russell O; Fan, Angela P; Zhao, Xudong; Hsu, Yunung; Gjiang, Yuhong; Huang, Lei; Li, Dan; Lu, Christopher; Ren, Yuanpeng; Jiang, Baisheng; Chen, Qi
Abstract: Background: Pronounced doctor–patient conflicts and physician attrition in China are thought to be secondary to inadequate training professionalism during medical school. We aimed to explore Chinese medical students and residents' perspectives on professional role formation. Methods: This exploratory study consisted of medical students and residents from 85 medical schools and teaching hospitals across China. A questionnaire was distributed for participants to rate 17 items that are important to professional role formation. We did statistical analyses using SPSS version 20. Ethical approval was obtained from the institutional review board of the principal investigator's institution. Findings: Of the 1746 medical students and residents included in this study, "morality and codes of behaviour" was viewed as the most important element of professionalism (n=480 [27·5%]), followed by "altruism" (n=427 [24·5%]), "integrity and honesty" (n=293 [16·8%]), "compassion and caring attitudes" (n=124 [7·1%]), and "social accountability" (n=119 [6·8%]). The elements perceived by medical students as most insufficiently taught in school were "integrity and honesty" (37·4% intention–action gap), followed by "morality and codes of behaviour" (24·4% intention–action gap). Interpretation: Physicians' professional role formation involves experience and reflection. What defines professionalism might differ between cultures, and this study indicated that Chinese medical society views "morality and codes of behaviour" as the highest value in the profession, although insufficiently taught. Rethinking and remediation of medical education would be helpful to strengthen a societal specific doctor–patient relationship. Funding: Republic of China Ministry of Science and Technology (MOST 105-2629-S-010-001).